Changes in the associations of race and rurality with SARS-CoV-2 infection, mortality, and case fatality in the United States from February 2020 to March 2021: A population-based cohort study - George N. Ioannou (Public Library of Science (PLoS), 2021)
Background We examined whether key sociodemographic and clinical risk factors for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection and mortality changed over time in a population-based cohort study. Methods and findings In a cohort of 9,127,673 persons enrolled in the United States Veterans Affairs (VA) healthcare system, we evaluated the independent associations of sociodemographic and clinical characteristics with SARS-CoV-2 infection (n = 216,046), SARS-CoV-2–related mortality (n = 10,230), and case fatality at monthly intervals between February 1, 2020 and March 31, 2021. VA enrollees had a mean age of 61 years (SD 17.7) and were predominantly male (90.9%) and White (64.5%), with 14.6% of Black race and 6.3% of Hispanic ethnicity. Black (versus White) race was strongly associated with SARS-CoV-2 infection (adjusted odds ratio [AOR] 5.10, [95% CI 4.65 to 5.59], p-value <0.001), mortality (AOR 3.85 [95% CI 3.30 to 4.50], p-value < 0.001), and case fatality (AOR 2.56, 95% CI 2.23 to 2.93, p-value < 0.001) in February to March 2020, but these associations were attenuated and not statistically significant by November 2020 for infection (AOR 1.03 [95% CI 1.00 to 1.07] p-value = 0.05) and mortality (AOR 1.08 [95% CI 0.96 to 1.20], p-value = 0.21) and were reversed for case fatality (AOR 0.86, 95% CI 0.78 to 0.95, p-value = 0.005). American Indian/Alaska Native (AI/AN versus White) race was associated with higher risk of SARS-CoV-2 infection in April and May 2020; this association declined over time and reversed by March 2021 (AOR 0.66 [95% CI 0.51 to 0.85] p-value = 0.004). Hispanic (versus non-Hispanic) ethnicity was associated with higher risk of SARS-CoV-2 infection and mortality during almost every time period, with no evidence of attenuation over time. Urban (versus rural) residence was associated with higher risk of infection (AOR 2.02, [95% CI 1.83 to 2.22], p-value < 0.001), mortality (AOR 2.48 [95% CI 2.08 to 2.96], p-value < 0.001), and case fatality (AOR 2.24, 95% CI 1.93 to 2.60, p-value < 0.001) in February to April 2020, but these associations attenuated over time and reversed by September 2020 (AOR 0.85, 95% CI 0.81 to 0.89, p-value < 0.001 for infection, AOR 0.72, 95% CI 0.62 to 0.83, p-value < 0.001 for mortality and AOR 0.81, 95% CI 0.71 to 0.93, p-value = 0.006 for case fatality). Throughout the observation period, high comorbidity burden, younger age, and obesity were consistently associated with infection, while high comorbidity burden, older age, and male sex were consistently associated with mortality. Limitations of the study include that changes over time in the associations of some risk factors may be affected by changes in the likelihood of testing for SARS-CoV-2 according to those risk factors; also, study results apply directly to VA enrollees who are predominantly male and have comprehensive healthcare and need to be confirmed in other populations. Conclusions In this study, we found that strongly positive associations of Black and AI/AN (versus White) race and urban (versus rural) residence with SARS-CoV-2 infection, mortality, and case fatality observed early in the pandemic were ameliorated or reversed by March 2021. George Ioannou and co-workers study the distribution of SARS-CoV-2 infections and outcomes among the United States population. Author summary Why was this study done? As the Coronavirus Disease 2019 (COVID-19) pandemic continues to evolve, some risk factors for infection with COVID-19 and death due to COVID-19 that were described early in the pandemic may be changing. Recognizing such changes is important in informing population-based approaches to prevent infection and reduce mortality. What did the researchers do and find? We investigated how the associations of key sociodemographic and clinical factors with COVID-19 infection, mortality, or case fatality changed between February 2020 and March 2021 among a cohort of approximately 9.1 million persons enrolled in the national US Veterans Affairs (VA) healthcare system, including 216,046 who tested positive and 10,230 who died of COVID-19 during the study period. Black (versus White) race was strongly associated with a 5-fold higher risk of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection, a 4-fold higher risk of mortality, and a 2.5-fold higher risk of case fatality in February to March 2020, but these associations attenuated over time and were no longer statistically significant by November 2020 for infection and mortality and were reversed for case fatality. American Indian/Alaska Native (AI/AN versus White) race was associated with SARS-CoV-2 infection early in the pandemic, but this association declined over time and reversed by March 2021. Urban (versus rural) residence was associated with 2-fold higher risk of infection, a 2.5-fold higher risk of mortality, and 2.2-fold higher risk of case fatality in February to April 2020, but these associations attenuated over time and reversed by September 2020. Throughout the observation period, high comorbidity burden, younger age, Hispanic ethnicity, and obesity were consistently associated with infection, while high comorbidity burden, older age, Hispanic ethnicity, and male sex were consistently associated with mortality. What do these findings mean? Early in the pandemic, there were strongly positive associations of Black and AI/AN (versus White) race and urban (versus rural) residence with SARS-CoV-2 infection, mortality, and case fatality, but these were ameliorated or even reversed by March 2021. Our results apply directly to VA enrollees who are predominantly male and have access to universal healthcare; they need to be confirmed in other populations.